Chloride movements across cellular membranes - Pusch, Michael; ScienceDirect eBooks (Amsterdam : Boston : Elsevier, 2007)
All living cells are surrounded by a lipidic membrane that isolates them from the often harsh environment. However, to take up nutrients, to excrete waste, and to communicate among each other, Nature has invented an incredibly diverse set of transmembrane transport proteins. Specialized transporters exist to shuttle electrically charged ions, positive cations like sodium or negative anions like chloride, across the membrane. In the recent years, tremendous progress has been made in the field of chloride transport. The present book presents the state of the art of this rapidly expanding and interest-gaining field of membrane transport. It is addressed at a broad medically, physiologically, biologically, and biophysically interested readership. Describes the state-of-the-art in anion transport research. Written by leaders in the field. Presents a timely discussion of this rapidly emerging and expanding field.
Chloride-Transporting Proteins in Mammalian Organisms: An Overview -- Physiological Functions of the CLC Chloride Transport Proteins -- Structure and Function of CLC Chloride Channels and Transporters -- Pharmacology of CLC Chloride Channels and Transporters -- The Physiology and Pharmacology of the CFTR Cl Channel -- Gating of Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel -- Functional Properties of Ca2[rho]-Dependent Cl- Channels and Bestrophins: Do They Correlate? -- Cell Volume Homeostasis: The Role of Volume-Sensitive Chloride Channels -- GABAergic Synaptic Transmission -- Physiology of Cation- Chloride Cotransporters -- Plasma Membrane Cl-/HCO3- Exchange Proteins -- Orchestration of Vectorial Chloride Transport by Epithelia.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Biological transport; Chloride cells; GABA; Biological Transport; Chloride Channels; GABA Agents; Receptors, GABA -- physiology; SCIENCE -- Life Sciences -- Biochemistry; Biological transport; Chloride cells; GABA; Electronic books